Proceedings of the International Conference on Biology, Sciences and Education (ICoBioSE 2019) 2020
DOI: 10.2991/absr.k.200807.009
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Mahogany Stomata (Swietenia macrophylla K.) in Polluted Environments

Abstract: One of a plant that is usually used as a green roadside plant in the urban area is mahogany (Swietenia macrophylla K.). The influence of environmental pollution in plants can be seen from stomata in the leaves. This study was aimed to determine the characteristic of the mahogany leaf stomata in a polluted environment. The observed characteristics were a type of stomata, density and distribution stomata. The research was conducted in March to July 2019 in the Botanical Laboratory, Faculty of Mathematics and Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
0
5
0
5
Order By: Relevance
“…Raven et al (2011) explained that mostly the number of stomata was found on the leaf abaxial surface as a mechanism for adaptation of trees to environments with high temperatures to reduce overtranspiration. Des et al (2020) confirmed the presence of Mahogany leaf stomata which were only on the leaf abaxial side. Alege & Shaibu (2015) also confirmed that the stomata of Flamboyant (Delonix regia) as well as other members of Fabaceae such as Parkia biglobosa, Senna siamea (Johar), Daniella oliveriand, and Caesalpinia pulcherrima were only found on the abaxial surface.…”
Section: Total Of Individuals 138mentioning
confidence: 54%
See 2 more Smart Citations
“…Raven et al (2011) explained that mostly the number of stomata was found on the leaf abaxial surface as a mechanism for adaptation of trees to environments with high temperatures to reduce overtranspiration. Des et al (2020) confirmed the presence of Mahogany leaf stomata which were only on the leaf abaxial side. Alege & Shaibu (2015) also confirmed that the stomata of Flamboyant (Delonix regia) as well as other members of Fabaceae such as Parkia biglobosa, Senna siamea (Johar), Daniella oliveriand, and Caesalpinia pulcherrima were only found on the abaxial surface.…”
Section: Total Of Individuals 138mentioning
confidence: 54%
“…The observed parameters were distribution, type, length and width of stomata, length and width of pores, number of stomata, and density of stomata, which were observed in the wide field of view (400x magnification). Determination of stomatal density was calculated by formula (1) from Willmer (1983) in Des et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upaya penyembuhan penyakit karena infeksi yang diakibatkan oleh E. coli diperlukan suatu obat yang mempunyai efek samping kecil, namun daya kerja optimal.2 Antibiotik sudah banyak digunakan terutama dalam menghambat mikroorganisme yang berhubungan dengan infeksi (3,4). Penelitian Kibret dkk, melaporkan bahwa E. coli memiliki tingkat resistensi yang tinggi terhadap eritromisin (89,4%),amoksisilin (86,0%), tetrasiklin (72,6%), gentamisin (58%), betalaktam (35,5%) (5). [1] Resistensi antibiotik dikaitkan dengan penggunaan berlebihan dan penyalahgunaan obat-obatan dan peresepan secara tidak rasional, serta kurangnya pengembangan obat baru oleh industri farmasi (6).…”
Section: Aunclassified
“…The University of Sumatera Utara (USU) campus, as one of the universities green space in Medan, provides an open open space with various vegetation to serve out its function as a microclimate controller and provide clean air for the surrounding community. Cities, industry, and transportation all became major contributors to urban air pollution [7]. As urban air pollution increases, green open spaces become increasingly important because they can reduce air pollution by absorbing various pollutants [8].…”
Section: Introductionmentioning
confidence: 99%